2021
DOI: 10.1080/23311975.2021.1968206
|View full text |Cite
|
Sign up to set email alerts
|

The impact of online shopping attributes on customer satisfaction and loyalty: Moderating effects of e-commerce experience

Abstract: The COVID-19 pandemic has expedited the growth of e-commerce in South Africa, as in global markets, strengthening online shopping exchange relationships. Businesses seek advanced models of the online shopping dimensions that are appropriate for tailoring services to customers. The data collected included customers' perceived information quality, privacy concerns, perceived security, product variety, and product delivery as antecedents of customer satisfaction, while information quality and satisfaction were sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 94 publications
(212 reference statements)
7
74
2
4
Order By: Relevance
“…It is also expected to stimulate consumers to shop at the store. Consumers may store services that have a major impact on the evaluation of their services and products (Erdil, 2015;Mofokeng, 2021). Stores can also uphold accountability for the information and sights that catch their eye.…”
Section: Store Environment -Impulse Buyingmentioning
confidence: 99%
“…It is also expected to stimulate consumers to shop at the store. Consumers may store services that have a major impact on the evaluation of their services and products (Erdil, 2015;Mofokeng, 2021). Stores can also uphold accountability for the information and sights that catch their eye.…”
Section: Store Environment -Impulse Buyingmentioning
confidence: 99%
“…The fulfilment phase mainly concerns delivery of products to their final destinations in an efficient and effective manner (Ascarza et al 2017) and includes product returns (Nguyen et al 2019). Research has indicated that the delivery of products has a strong impact on customer satisfaction in e-commerce (Mofokeng 2021), and that as many as 85% of customers have selected online retailers based on their delivery service reliability and trustworthiness (UPS 2021). This research focuses on the fulfilment part of online transactions because it is an important success factor in e-commerce and because of the wide variety of related factors that influence the behaviour of consumers buying online.…”
Section: Logistics Capabilities Influencing Online Purchasing Behaviourmentioning
confidence: 99%
“…The protective measures adopted by retailers against the COVID-19 virus significantly and positively influenced customer safety during shopping, their attitudes and satisfaction, which resulted in an increase of their behavioral intentions towards new integrated forms of digital and face-to-face shopping (Untaru & Han, 2021;Kazancoglu & Demir, 2021). Retailers are expected to re-design their business settings and adopt protective and preventive measures to encourage visitation of their stores (Filimonau et al, 2021), to improve customer satisfaction towards web stores (Mofokeng, 2021;Thaipradit & Tantong, 2021).…”
Section: Changes In Retail Consumer Behaviormentioning
confidence: 99%